Acceleration and curricular enrichment for gifted students: a perspective of the situation in Peru - Madrid Valdiviezo, Jazmin (2018)
It is proposed to theoretically review the main strategies of acceleration and curricular enrichment aimed at gifted students. Information has been sought nationally and internationally and some strategies have been compiled that have demonstrated to be useful for time use and the enhancement of academic talent. The question at issue has been scarcely worked in the country, providing evidence lack of interest from academics, as well as the Peruvian education system. Emphasis is placed on the importance that parents and teachers being able to know and select effective alternatives to attend the needs of the most capable students. Finally, the subject is discussed from a psychoeducational and rights perspective, framed in the Peruvian context.